Biochemical Regulation of the Glyoxalase System in Response to Insulin Signaling - Der-Yen Lee; Yu-Chin Lin; Geen-Dong Chang (MDPI AG, 2021)
Methylglyoxal (MG) is a reactive glycation metabolite and potentially induces dicarbonyl stress. The production of MG in cells is increased along with an increase in carbohydrate metabolism. The efficiency of the glyoxalase system, consisting of glyoxalase 1 (GlxI) and glyoxalase 2 (GlxII), is crucial for turning the accumulated MG into nontoxic metabolites. Converting MG-glutathione hemithioacetal to S-d-lactoylglutathione by GlxI is the rate-determining step of the enzyme system. In this study, we found lactic acid accumulated during insulin stimulation in cells, however, cellular MG and S-d-lactoylglutathione also increased due to the massive flux of glycolytic intermediates. The insulin-induced accumulation of MG and S-d-lactoylglutathione were efficiently removed by the treatment of metformin, possibly via affecting the glyoxalase system. With the application of isotopic 13C3-MG, the flux of MG from extracellular and intracellular origins was dissected. While insulin induced an influx of extracellular MG, metformin inhibited the trafficking of MG across the plasma membrane. Therefore, metformin could maintain the extracellular MG by means of reducing the secretion of MG rather than facilitating the scavenging. In addition, metformin may affect the glyoxalase system by controlling the cellular redox state through replenishing reduced glutathione. Overall, alternative biochemical regulation of the glyoxalase system mediated by insulin signaling or molecules like biguanides may control cellular MG homeostasis.